Pengaruh Perubahan Kecepatan Pemakanan Terhadap Kekasaran Permukaan Pada Proses Pembubutan - Hadimi Hadimi (Universitas Muhammadiyah Yogyakarta, 2008)
This research done to know existence of transformation influence of feeding speed at turning process to surface roughness of work substance. Specimen material is ST 37 with Ø 30, 40, 50 and 70 mm, with transformation of feeding speed 0,05, 0,069, 0,088, 0,125 and 0,17(mm/rev), depth of feed 0,2 mm, and speed of revolution of engine 950 rpm. Then the several assaying of surface roughness level of the specimen and calculation statistic by using one way variant analytical method based on data result of assaying. Result of research indicates that existence of influence significant to surface roughness value caused by transformation of feeding speed at specimen turning process Ø 30, 40, 50 and 70 mm, ST 37 material with depth of feed 0,25 mm and revolution of engine 950 rpm. Average of smallest roughness value is at Ø 30 mm yielding best surface roughness. This thing indicates that feeding speed and substance diameter lathed influential to surface roughness value.